Exploring Adaptation Strategies Of Pre-Service English Teachers During PPL at Junior High School Implementing the Kurikulum Merdeka - Lutfiyah Lutfiyah (Proceeding of the International Conference on Global Education and Learning, 2024)
This study explored the adaptation strategies of pre-service English teachers during their teaching practicum (PPL) in junior high schools implementing the Kurikulum Merdeka framework. The aim of the study is to explore how pre-service English teachers integrate the flexible and student-centered curriculum while adjusting to a variety of problems in a real-world classroom environment. Semi-structured interviews and non-participant observations were used in this qualitative study to collect data from six pre-service teachers. The results showed that pre-service teachers used a variety of strategies to deal with procedural, managerial, psychological, instructional, and cultural obstacles, such as reflective practices, collaborative mentoring, and differentiated instruction. In addition to highlighting the necessity of successfully promoting Kurikulum Merdeka, the study emphasizes the value of mentorship and reflective practices in promoting professional development. These findings help to enhance programs for preparing future teachers and offer insightful advice to pre-service English teachers as they enter into professional teaching roles.